NUMERICAL INVESTIGATION HEAT TRANSFER OF ROTARY DRYER OLIVE LEAF DRYING USING COMPUTATIONAL FLUID DYNAMICS METHOD - carles, Henry carles; Ramadhan, Daris Fajar (Universitas Mercu Buana, 2024)
The conventional drying process for olive leaves is done in the sun. The drying capacity is relatively small over a long period. This process can be improved by using a rotary dryer. To determine optimal drying conditions in the temperature range of 30-45 [ºC], it is necessary to carry out numerical analysis using the Computational fluid dynamics method with varying heating temperatures of 30, 40, 50, and 60 [ºC]. The total heat energy transferred from the heater to the olive leaves by convection is 366,252 [kJ/s] and 21,371 [kJ/s] by conduction with a rotary dryer rotation speed of 75 [rpm]. The drying temperatures resulting from these four variations are 25.65, 26.85, 29.55, and 31.35 [ºC] with a heat flux of 2.542 x 10-6 [W/m2]. The heating temperature of the rotary dryer set at 60 [ºC] can distribute the heat of 1.8 [M.J.], resulting in an optimal olive leaf drying temperature of 31.35 [ºC].